HUMAN RIGHTS IN HUMANITARIAN CONTEXTS: SOCIO-PSYCHOLOGICAL ANALYSIS OF PERSONAL SECURITY IN THE EXPERIENCE OF SOCIAL TRAUMA - Zhanna Virna; Ana Maria Eyng (Психологічні перспективи)
Purpose. The purpose of the presented article is to provide an analytical review of the findings of a research project on personal safety in the context of experiencing social trauma based on the materials of a research internship within the framework of the Postgraduate Education and Humanities Programme (PUCPR, Curitiba, Brazil).